If it's not what You are looking for type in the equation solver your own equation and let us solve it.
50-3(2x-3)+2(2x-1)=23
We move all terms to the left:
50-3(2x-3)+2(2x-1)-(23)=0
We add all the numbers together, and all the variables
-3(2x-3)+2(2x-1)+27=0
We multiply parentheses
-6x+4x+9-2+27=0
We add all the numbers together, and all the variables
-2x+34=0
We move all terms containing x to the left, all other terms to the right
-2x=-34
x=-34/-2
x=+17
| (3x-2)/3+(2x+3)/3=x+7/6 | | 3x(-7)=8x+4 | | 3(y-1/3)=2(2y-6 | | -4x+6=-x2+5 | | x-4/2=0 | | -4x+6=-2+5 | | X+1÷x=17÷4 | | p+26=15 | | s-6=-9 | | 2x+7+8x=35 | | 7x+11=-150 | | 15*x=216 | | 16*x=216 | | 18y+4=10y= | | 6-5x-1.5=-24x+1.6 | | 10x^2-6x+6=0 | | F=2.25d+1.5. | | x*2x*3x=900 | | x3-2x2+2x-1=0 | | 5/9x+23=-12 | | 7(4w+5)=0/5 | | 3x^-2x-5=0 | | 6x+1=0x+2 | | 6x+2=1x+4 | | 6x+9=2x+0 | | x^-18x+45=0 | | b+2b-9=3 | | 4.5+2x=14 | | 55/6n=10 | | 5-5y=0 | | 0.05x=1.5+0.8x | | 135°=180°(n-2)÷n |